2016
DOI: 10.14723/tmrsj.41.155
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth of GaN on SiC substrates with femtosecond-laser-induced periodic nanostructures

Abstract: A 6H-SiC substrate with femtosecond-laser-induced periodic nanostructures was used as an underlayer for GaN growth. GaN nuclei were formed on the periodic nanostructure selectively. The in-plane direction of GaN was dependent on the in-plane direction of the SiC substrate, and no dependent on the direction of the periodic nanostructures or laser scanning. We suggest that the fine structure and high wettability at the region of the periodic nanostructure enhanced the adsorption of GaN nuclei preferentially. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The direction of the periodic nanostructures was perpendicular to the polarization direction of the incident laser. According to previous research, 6) the direction of the periodic nanostructures is dependent on the laser polarization and not on the in-plane direction of the SiC substrate or the direction of laser scanning. At high laser peak intensity (i.e., at high average laser power or at low repetition frequency) calculated using Eq.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The direction of the periodic nanostructures was perpendicular to the polarization direction of the incident laser. According to previous research, 6) the direction of the periodic nanostructures is dependent on the laser polarization and not on the in-plane direction of the SiC substrate or the direction of laser scanning. At high laser peak intensity (i.e., at high average laser power or at low repetition frequency) calculated using Eq.…”
Section: Resultsmentioning
confidence: 90%
“…[1][2][3] Recently, periodic nanostructures, formed using femtosecond-laser irradiation, have attracted much interest as laser-induced periodic surface structures (LIPSS). [4][5][6][7][8][9][10][11][12][13][14][15][16] The periodicity of the nanostructures thus formed is less than the wavelength of the incident laser. Several LIPSS-formation mechanisms have been proposed, including the excitation of surface plasmon polaritons (SPPs), [7][8][9][10][11][12] second harmonic generation (SHG), [13][14][15] and a parametric-decay process.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding results appeared when irradiating SiC or Si. 3,30) Furthermore, the cracks tend to form perpendicular to the LIPSS and the {1-100} GaN or {11-20} GaN faces are exposed. The depth of the v-shaped ablation trench does not depend much on the in-plane crystal direction, which showed a difference of only 5% between directions.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported on the formation of laser-induced periodic surface structure (LIPSS) in SiC. 3,4) LIPSSs have a periodicity that is shorter than the wavelength of the incident laser beam, and they are self-formed by the laser irradiation alone, without a mask. [5][6][7][8][9][10][11] Several LIPSS formation mechanisms, including the excitation of surface plasmon polaritons, [6][7][8] a parametric decay process, 8,9) and second harmonic generation, 10,11) have been proposed and have shown results consistent with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced periodic structures with a periodicity smaller than the incident laser wavelength have been studied in recent years. [10][11][12][13][14][15][16][17][18][19][20][21][22] In these studies, the signature structures have been found to (i) be created by self-formation on the surface; (ii) possess a periodicity less than the wavelength of the incident laser; and (iii) possess a structure direction that is dependent on the laser polarization. Several nanostructureformation mechanisms have been proposed, including excitation of surface plasmon polaritons (SPPs), [13][14][15][16][17][18] SHG [19][20][21] and parametric-decay processes.…”
Section: Methodsmentioning
confidence: 99%